Analyzing The Mediating Role of User Satisfaction between The Antecedents of Playing Online Games and User Loyalty - Rani, S Dilli; Selvasundaram, K (International Journal of Accounting and Economics Studies, 2025)
The primary objective of this study is to investigate the mediating role of user satisfaction in the relationship between the antecedents of online game playing and user loyalty. The analysis of this study was conducted using the 200 collected samples. The responses for variables are collected using a five-point Likert scaling technique. The reliability and validity of the collected samples were initially tested, followed by main tests such as regression analysis and mediation analysis. The indirect and direct effect is analyzed to find the mediating role of user satisfaction between antecedents of playing online games and user loyalty. The full mediation is found between user loyalty and the factors of cognition, socialization, and earning. Through user satisfaction, the achievement, socialization, and earning elements have an indirect mediation influence on user loyalty. Therefore, to achieve the required developments, game creators must take user reviews, feedback, and recommendations into consideration.